Răspuns :
tg B= tg 60°
m(<C) =90°-m(<B) =90°-60°=30°
AB=BC/2= 12/2=6 cm
tg B=√3
tg B = AC/AB
√3=AC/6
AC=6√3 cm
m(<C) =90°-m(<B) =90°-60°=30°
AB=BC/2= 12/2=6 cm
tg B=√3
tg B = AC/AB
√3=AC/6
AC=6√3 cm
tg B = rad3 ⇒ B=60° ⇒ C=30°
Ip. BC=12 cm ⇒ cateta opusa ∡30°, adica AB= jumatate din ipotenuza = 6 cm
AC=rad(BC^2-AB^2) = rad(144-36) = rad108=rad(2^2 * 3^3) = 6rad3 cm.
Figura o faci singur/a. Este f usor.
Ip. BC=12 cm ⇒ cateta opusa ∡30°, adica AB= jumatate din ipotenuza = 6 cm
AC=rad(BC^2-AB^2) = rad(144-36) = rad108=rad(2^2 * 3^3) = 6rad3 cm.
Figura o faci singur/a. Este f usor.